2021
DOI: 10.1038/s41598-021-97128-3
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of natural history museums in advancing eDNA for biodiversity studies: a case study with Amazonian fishes

Abstract: Ichthyological surveys have traditionally been conducted using whole-specimen, capture-based sampling with varied but conventional fishing gear. Recently, environmental DNA (eDNA) metabarcoding has emerged as a complementary, and possible alternative, approach to whole-specimen methodologies. In the tropics, where much of the diversity remains undescribed, vast reaches continue unexplored, and anthropogenic activities are constant threats; there have been few eDNA attempts for ichthyological inventories. We te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Overall, FARMS are a simple, standardized, broadly accessible 2022, no other specimens of P. laurae had been observed or collected (Baldwin et al, 2018;Tornabene et al, 2016). This suggests that deploying FARMS in undersampled habitats such as deep reefs may yield a additional taxonomic records that help us gain a better understanding of cryptobenthic fish diversity and distribution patterns, while also yielding critically important specimens and tissue samples that can support emerging molecular survey methods (de Santana et al, 2021;Gold et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, FARMS are a simple, standardized, broadly accessible 2022, no other specimens of P. laurae had been observed or collected (Baldwin et al, 2018;Tornabene et al, 2016). This suggests that deploying FARMS in undersampled habitats such as deep reefs may yield a additional taxonomic records that help us gain a better understanding of cryptobenthic fish diversity and distribution patterns, while also yielding critically important specimens and tissue samples that can support emerging molecular survey methods (de Santana et al, 2021;Gold et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…eDNA studies carried out so far on the Neotropical ichthyofauna [ 25 28 ], although limited by the size of the reference database for the mitochondrial gene 12S used, have faced varying degrees of success. Jackman et al (2021) identified 84 molecular taxonomic units (MOTU), of which only 4 to the species level (1.6%), out of the 258 fish species detected using traditional sampling methods in the Adolpho Ducke Forest Reserve near Manaus in the Brazilian Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…Very few eDNA studies were carried out so far on the ichthyofauna of the Neotropics (e.g. [ 25 28 ]), and even fewer in the most species-rich basin of the Neotropics: the Amazon basin [ 27 , 28 ]. All these studies were limited by the size of the reference database.…”
Section: Introductionmentioning
confidence: 99%
“…Whichever approach is used, they all ultimately rely on the accuracy and completeness of a reference database for subsequent taxonomic assignment (Dugal et al, 2022; Jackman et al, 2021). Reference databases therefore should be a major consideration of any metabarcoding study as they underpin the successful and accurate taxonomic assignments (de Santana et al, 2021; Rodríguez‐Ezpeleta et al, 2021). Ideally, these databases consist of verified barcodes, including taxa known to occur in the study area (Taberlet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%